Penatalaksanaan Fisioterapi Pada Frozen Shoulder Et Causa Capsulitis Adhesiva Dengan Metode Manual Theraphy - Putri, Herlin Kartika Buana, - (2021)
In everyday life, humans cannot be separated from the use of physical capacity and functional ability which is a full integration of the body's systems. The emergence of several complaints also often accompanies human movement activities due to gaps in body function when moving. The complaints that often occur in motion and function in the shoulder joint are basically pain and stiffness that result in limited motion in the shoulder joint (Morgan & Potthoff, 2012). The study entitled "Physiotherapy Management of Frozen Shoulder et Causa Capsulitis Adhesiva with the Manipulation method. Theraphy ". The purpose of this study was to determine the addition of Joint Area of Motion (LGS), and to determine the effectiveness of Manual Therapy for Adhesiva Capsulitis patients. The research method used is to add the Manual Therapy technique by collecting patients randomly or by collecting questionnaires. The role of physiotherapy in this case is to reduce physical problems and improve functional abilities. Physiotherapy intervention is in the form of Manual Therapy, and education as a home exercise program. In this study, patients were given two to three times therapy in one week, so that there was a decrease in pain and an increase in the area of motion of the joints.